Pengaruh Citra Merek dan Loyalitas Merek Terhadap Ekuitas Merek Susu Cair Dalam Kemasan Kotak Indomilk di Kota Padang - Vidhara Islamia; Okki Trinanda (Jurnal Salingka Nagari, 2023)
The purpose of this research is to determine the effect of brand image and brand loyalty on brand equity of liquid milk packaged in Indomilk boxes at Padang City. This type of research is causative. The population of the research is the people of the city of Padang. The Number of research samples was 97 people and selected using purposive sampling technique. The data used is the type of primary data obtained through the distribution of questionnaires to the people of the city of Padang with predetermined criteria. The analytical method is multiple regression analysis using SPSS 16. The results indicate that (1) brand image has a significant effect on brand equity, (2) brand loyalty has a significant effect on brand equity, (3) brand image and brand loyalty have a significant effect on brand equity.